Wind generator-energy storage control schemes for autonomous grid - Fazeli, Meghdad (2011)
Conventionally the power network operators were obliged to buy all the wind energy generated by wind farms. However, as the penetration of wind energy (or generally any other sort of renewable source) in a power system is increased, the ability of other generators to balance the demand becomes limited. This will necessitate the control of wind turbines in order to generate a given demand power rather than extracting the maximum wind power. This control approach is termed “Power Demand Control” in this thesis. In contrast to Power Demand Control, “Power Smoothing Control” utilizes energy storage systems in order to absorb high frequency wind fluctuations, hence, delivering a smoother version of wind power into the grid/load. The drawback of the Power Smoothing approach is that the average power into the grid/load is still determined by the available wind power rather than the system operator. The Power Demand Control approach, which has received little attention in literatures, is the main focus of this thesis. This research proposes control schemes with and without external energy storage for the Power Demand Control strategy.